Incorporating shared decision making into communication with older adults with cancer and their caregivers: Development and evaluation of a geriatric shared decision-making communication skills training module. Issue 11 (November 2020) - Shen, Megan Johnson; Manna, Ruth; Banerjee, Smita C.; Nelson, Christian J.; Alexander, Koshy; Alici, Yesne; Gangai, Natalie; Parker, Patricia A.; Korc-Grodzicki, Beatriz
Highlights: Shared decision making for older adults include patient, caregiver, and provider. There is a need for communication training for working with older adults. This intervention is acceptable, feasible, and potentially effective. Abstract: Objective: The purpose of this study was to evaluate a Communication Skills Training (CST) module for health care providers (HCPs) applying a shared decision-making approach to a meeting with an older adult with cancer and his/her family. Methods: Ninety-nine HCPs from community-based centers, cancer centers, and hospitals in the Northeastern U.S. who worked primarily with older adult patients participated in a CST module entitled Geriatric Shared Decision Making . Participants completed pre- and post-training Standardized Patient Assessments (SPAs) and a survey on their confidence in and intent to utilize skills taught. Results: Results indicated high HCP satisfaction with the module, with over 95 % of participants reporting high endorsement to all five evaluation items. HCPs' self-efficacy in utilizing communication skills related to geriatric shared decision making significantly increased pre- to post-training. In standardized patient assessments among a subset of providers (n = 30), HCPs demonstrated improvements in three shared decision-making skills: declare agenda, invite agenda, and check preference. Conclusion: A geriatric shared decision-making CST workshop for HCPs showed feasibility, acceptability, and improvement in self-efficacy as well as skill uptake. Practice implications: This Geriatric Shared Decision-Making CST module provides an intervention for improving provider-patient-family member communication in the context of cancer care for older adults.